Respuesta :

gmany

Answer:

x = -12 and y = -12 → (-12, -12)

Step-by-step explanation:

[tex]\left\{\begin{array}{ccc}y=\dfrac{1}{2}x-6&(1)\\3x-4y=12&(2)\end{array}\right\\\\\text{Substitute (1) to (2):}\\\\3x-4\left(\dfrac{1}{2}x-6\right)=12\qquad\text{use the distributive property}\\\\3x+(-4)\left(\dfrac{1}{2}x\right)+(-4)(-6)=12\\\\3x-2x+24=12\qquad\text{subtract 24 from both sides}\\\\\boxed{x=-12}\\\\\text{Put the value of x to (1)}\\\\y=\left(\dfrac{1}{2}\right)(-12)-6\\\\y=-6-6\\\\\boxed{y=-12}[/tex]